CATALYST FOR PRODUCING ISOPROPYLBENZENE AND ITS PRODUCTION AND USE - Patent application

A palladium-based catalyst with phosphorus and silica support improves isopropylbenzene production from α,α-dimethylbenzyl alcohol, addressing activity, selectivity, and stability issues, and minimizing environmental pollution.

JP7599484B2Active Publication Date: 2024-12-13CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022519509
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-17
Filing Date
2020-09-29
Publication Date
2024-12-13
Estimated Expiration
2040-09-29

AI Technical Summary

Technical Problem

Existing methods for producing isopropylbenzene from α,α-dimethylbenzyl alcohol face challenges in catalyst activity, selectivity, stability, and environmental pollution, particularly due to the use of chromium and inadequate control of polymerization and hydrogenation reactions.

Method used

A supported palladium catalyst with phosphorus and/or its oxide as a modifying auxiliary component, combined with silica or alumina as a carrier, enhances catalyst activity and selectivity, and includes sulfur-containing compounds to improve hydrothermal stability and control excessive hydrogenation.

Benefits of technology

The catalyst achieves high conversion rates (>99.5%) and selectivity (>99.8%) of isopropylbenzene while reducing environmental impact and maintaining catalyst stability over extended periods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599484000012
    Figure 0007599484000012
  • Figure 0007599484000001
    Figure 0007599484000001
  • Figure 0007599484000002
    Figure 0007599484000002
Patent Text Reader

Abstract

The present invention provides a catalyst for producing isopropylbenzene, as well as a method for producing and using the catalyst. The catalyst includes a support and an active component supported on the support. The support includes a support substrate and a modifying auxiliary component supported on the support substrate. The active component includes metallic palladium and / or its oxide, and the modifying auxiliary component is phosphorus and / or its oxide. Optionally, the active component further includes metallic copper and / or its oxide. The catalyst further includes a sulfur-containing compound. When used in the production of isopropylbenzene, the catalyst of the present invention can better suppress local overheating of the catalyst caused by the relatively high initial activity of the catalyst, avoiding the growth of metal particles and excessive hydrogenation of isopropylbenzene to isopropylcyclohexane. Meanwhile, it effectively controls the production of dimerized isopropylbenzene, significantly improving the operational stability of the catalyst while increasing the selectivity of isopropylbenzene.
Need to check novelty before this filing date? Find Prior Art

Description

Detailed Description of the Invention

[0001] [Technical field] The present invention relates to a catalyst for producing isopropylbenzene, in particular to a catalyst for producing isopropylbenzene by using α,α-dimethylbenzyl alcohol (DMBA), and its production method and use. [Background technology] Propylene oxide (abbreviated as PO) is an important organic industrial chemical material, which is mainly used in the production of polyether polyol, propylene glycol, propanediol ether, etc., accounting for about 70% of the consumption of polyether polyol. At present, commercialized processes for the production of PO mainly include chlorohydrin processing, co-oxidation processing (PO / SM) and isopropylbenzene hydroperoxide recycle processing (CHP). CHP processing has the following advantages: the conversion rate and selectivity of the entire process are very high; the processing only results in PO products and is not affected by the price fluctuations of styrene by-products, which can bring more stable economic benefits to manufacturers; the technical processing is relatively simple, and the fixed investment is two-thirds that of PO / SM processing. In addition, the requirements for corrosion resistance of equipment in CHP processing are relatively low. In the production technology of propylene oxide by CHP processing, a large amount of α,α-dimethylbenzyl alcohol (DMBA) is generated in the process of propylene epoxy processing. α,α-dimethylbenzyl alcohol needs to be hydrogenated to produce isopropylbenzene for re-addition to the reaction cycle.

[0002] US Patent US6646139B2 describes the use of α,α-dimethylbenzyl alcohol and H 2and a process for producing isopropylbenzene by catalytic hydrocracking with copper-Cr as catalyst. The conversion of α,α-dimethylbenzyl alcohol can be up to 99%, but the selectivity is less than 98%. In addition, the use of Cr element in the preparation of the catalyst will result in serious environmental pollution. Chinese patent CN101733093B reported that the reaction of alumina- or zeolite-supported metallic palladium, or the reaction of a mixture of palladium and Pt at a reaction temperature below 160°C, achieved a conversion of α,α-dimethylbenzyl alcohol of more than 99.5% and a selectivity of isopropylbenzene of more than 99.5%. The stronger acidity of the support in this patent notably led to the polymerization of methylstyrene, which is an intermediate product of the dehydration of α,α-dimethylbenzyl alcohol. This patent does not mention the technical problem of the stability of the catalyst. Chinese patent application CN104230640A reported that the reaction of alumina- or zeolite-supported metallic palladium, or the reaction of a mixture of palladium and Pt at a reaction temperature below 160°C, achieved a conversion of α,α-dimethylbenzyl alcohol of more than 99.5% and a selectivity of isopropylbenzene of more than 99.5%. The stronger acidity of the support in this patent notably led to the polymerization of methylstyrene, which is an intermediate product of the dehydration of α,α-dimethylbenzyl alcohol. This patent does not mention the technical problem of the stability of the catalyst. 2 It is shown that the use of the catalyst can achieve 100% conversion of α,α-dimethylbenzyl alcohol, but less than 98.5% selectivity for isopropylbenzene at a reaction temperature of 180°C.

[0003] A known method for producing isopropylbenzene is to dehydrate cumyl alcohol to alpha-methylstyrene in the presence of a dehydration catalyst, and hydrogenate alpha-methylstyrene to cumene in the presence of a hydrogenation catalyst (e.g., European Chemical News, Vol. 74, No. 19475-11, March 2001). Chinese patent CN1732139A discloses: providing cumyl alcohol and hydrogen to a dehydration catalyst to obtain a mixture containing the resulting alpha-methylstyrene and water and hydrogen; providing the mixture to a hydrogenation catalyst, where the reaction temperature and reaction pressure are selected so that the water contained in the alpha-methylstyrene solution after dehydration is not concentrated. The reaction temperature is preferably 150-300°C, and the reaction pressure is preferably 100-2000 kPa. When the temperature is lower than 150°C and the pressure is higher than 2000 kPa, water condensation may occur at the dehydration reaction outlet, which reduces the performance of the hydrogenation catalyst. However, the known methods cannot meet the requirements for low-cost and efficient production of isopropylbenzene.

[0004] Problems in the prior art include catalytic activity and selectivity that need to be further improved, insufficient stability and serious environmental pollution in the production of isopropylbenzene by catalyzing the dehydration and hydrogenation of α,α-dimethylbenzyl alcohol. [Summary of the invention] The present invention provides a high activity and high selectivity supported palladium catalyst with excellent catalytic activity and selectivity, excellent hydration resistance and good stability, in order to solve the technical problems of low activity and selectivity, insufficient stability and serious environmental pollution of the catalysts in the prior art.

[0005] One aspect of the present invention is to provide a catalyst for producing isopropylbenzene, in particular for producing isopropylbenzene from α,α-dimethylbenzyl alcohol, comprising a support and an active component supported on the support, the support comprising a support base and a reforming auxiliary component supported on the support base, the active component comprising metallic palladium and / or an oxide thereof, and the reforming auxiliary component comprising phosphorus and / or an oxide thereof.

[0006] The carrier substrate is not particularly limited here, and may be a common catalyst carrier in this field unless otherwise specified. In a preferred embodiment, the carrier substrate is at least one selected from the group consisting of silica, alumina and activated carbon, and is preferably alumina.

[0007] In a preferred embodiment, the support substrate has a pore size of 10 to 25 nm and a pore size of 50 to 180 nm. 2 / g, and more preferably the support substrate has a pore size of 12 to 18 nm and a specific surface area of ​​120 to 160 m 2 / g.

[0008] In a preferred embodiment, the content of metallic palladium and / or its oxide in the catalyst is 0.01-5 wt.%. In a further preferred embodiment, the content of metallic palladium and / or its oxide in the catalyst is 0.05-1 wt.%, for example 0.05-0.5 wt.%, based on the content of elemental palladium therein.

[0009] In the present invention, the source of metallic palladium is not particularly limited, and is preferably at least one selected from the group consisting of palladium chloride, palladium nitrate, and chloropalladium acid, but is not limited thereto.

[0010] In a preferred embodiment, the catalyst has a palladium dispersion of 5-10%, preferably 6.5-8.5%.

[0011] Here, the hydrogenolysis of α,α-dimethylbenzyl alcohol is a coupling of two steps, dehydration and hydrogenation. Research has found that dehydration is the crucial step of the reaction. Therefore, in order to improve the reaction rate of all reactions, the dehydration activity of the catalyst in the catalyst adjustment should be improved first. The dispersion of metal palladium has a certain relationship with its particle size. Generally, the larger the particle, the lower the dispersion. Research has also found that the Pd dispersion is not linearly related to the particle size, since TEM analysis showed that the particle size of Pd did not increase significantly on the catalyst with reduced dispersion. In addition, the appropriate particle growth of Pd catalyst is helpful to improve the reaction selectivity. Therefore, it is necessary to control the dispersion within a moderate range.

[0012] The dispersion of metallic Pd is measured by hydrogen-oxygen titration. The specific analytical steps include increasing the temperature of the catalyst to 120°C in a flow of hydrogen (heating rate 10°C / min); keeping the temperature constant for 2 hours; then increasing the temperature to 145°C; purging with argon for 1 hour; then decreasing the temperature to room temperature (in argon atmosphere). Oxygen chemisorption: At room temperature, oxygen is introduced by pulse into the sample tube until saturation; then purging with argon for 40 minutes. Hydrogen titration measurement: A quantitative pulse of hydrogen is performed using a 6-way feed valve (quantitative tube volume 0.3 mL). The amount of consumed hydrogen can be calculated based on the area difference between the front peak and the rear peak on the chromatographic device, and the dispersion of metallic Pd on the catalyst can then be calculated.

[0013] In a preferred embodiment, the active component further comprises an active auxiliary metal and / or an oxide thereof. Preferably, the active auxiliary metal is at least one selected from the group consisting of metallic copper, metallic zinc, metallic cobalt, metallic tin, metallic nickel and metallic silver, for example metallic copper. In a further preferred embodiment, the content of the active auxiliary metal and / or an oxide thereof in the catalyst is 0.0001-0.2 wt%, preferably 0.0007-0.2 wt%, based on the content of the auxiliary metal element therein.

[0014] In the present invention, the source of the active auxiliary metal is not particularly limited, and may be, for example, at least one selected from the group consisting of an active auxiliary metal chloride, an active auxiliary metal nitrate compound, an active auxiliary metal acetate compound, and the like, but is not limited thereto.

[0015] Pd-based bimetallic / polymetallic catalysts modified with active auxiliary metals (e.g., Cu) can improve the isopropylbenzene selectivity of the catalyst, especially in the initial stage. Preferably, the weight content of Pd in ​​the catalyst is greater than that of the active auxiliary metals (e.g., Cu), i.e., the weight ratio of Pd to the active auxiliary metals (e.g., Cu) is >1.

[0016] In a preferred embodiment, the content of the reforming auxiliary component (phosphorus and / or its oxide) in the catalyst is 0.2-20 wt %. In a further preferred embodiment, the content of the reforming auxiliary component (phosphorus and / or its oxide) in the catalyst is 1-15 wt %, more preferably 1-7 wt %, where the content of phosphorus and / or its oxide is based on the content of elemental phosphorus therein.

[0017] In the present invention, the phosphorus source is not particularly limited, and is preferably at least one selected from the group consisting of phosphoric acid, potassium dihydrogen phosphate, phosphorous acid, and calcium phosphate, but is not limited thereto.

[0018] Based on extensive experimental research, the present inventors have found that the modification of the support with phosphorus can significantly improve the hydrogenation activity and stability of the catalyst, especially the hydrothermal stability. In particular, the simultaneous introduction of active auxiliary components (active auxiliary metals) into the catalyst has a significant technical effect on the improvement of the conversion rate of α,α-dimethylbenzyl alcohol and the selectivity of isopropylbenzene.

[0019] In a preferred embodiment, when the support substrate is not silica, the modified auxiliary component may further comprise silica.

[0020] In the catalyst of the present invention, modification with silica (especially to modify the alumina support substrate) can improve the activity and stability of the catalyst, where alumina is preferably used as the support substrate.

[0021] In a preferred embodiment (wherein the support substrate is not silica), the content of silica in the catalyst is >0-60 wt%, preferably >0-40 wt%, for example >0-20 wt%, where the content of silica is based on its molecular content.

[0022] Here, the pore size of the catalyst increases after modification with silicon, which improves the diffusion rate of reactants and products, thereby improving conversion and selectivity.In addition, it has also been found that the silicon-containing catalyst has better dehydration activity, which helps to promote the rate of hydrocracking reaction.

[0023] In a preferred embodiment (wherein the support substrate is not silica), after modification with silicon, the molar ratio of silicon to phosphorus based on the elements is ≦20, preferably ≦10, more preferably ≦4, but not 0. The content of the phosphorus and / or its oxides modifying auxiliary component in the catalyst is 0.2-20 wt%, preferably 1-15 wt%, more preferably 1-7 wt%. The content of phosphorus and / or its oxides is based on the content of elemental phosphorus therein, and the silica content in the catalyst is >0-60 wt%, preferably >0-40 wt%, e.g., >0-20 wt%.

[0024] This can greatly improve the high-temperature hydrothermal stability of the catalyst. For example, the change in the specific surface area and average pore size of the catalyst after high-temperature hydrothermal treatment is significantly reduced. For example, the change in the specific surface area is preferably less than 30%, and the change in the average pore size is less than 20%; more preferably, the change in the specific surface area is less than 10%, and the change in the average pore size is less than 10%.

[0025] Here, the temperature of the high-temperature hydrothermal treatment is 100 to 300° C., and the treatment time is 20 to 300 hours.

[0026] The high temperature hydrothermal stability is determined according to the following steps: (a) Specific steps of high temperature hydrothermal treatment of catalyst: Disperse the catalyst in excess water; Then, place the catalyst together with water into a crystallization kettle; After sealing the crystallization kettle, place it in an oven at 200° C. for 240 hours.

[0027] (b) The method for determining the specific surface area and pore size of the catalyst includes the following specific analytical steps: The physical properties (e.g., specific surface area, pore size, pore volume, etc.) of the catalyst support and catalyst are analyzed by nitrogen physical adsorption (ASAP 2020M, Micromeritics). Before analysis and testing, the sample is degassed in vacuum at 300 °C for 3 hours to remove the adsorbed impurities and moisture in the sample. Then, the nitrogen adsorption-desorption isotherm of the test sample is analyzed under liquid nitrogen environment (-196 °C).

[0028] The specific surface area of ​​the sample (S BET ) is the relative pressure P / P in the range of 0.05 to 0.20 0 and is calculated based on the nitrogen adsorption data by the BET equation (3-1):

[0029]

number

[0030] where P is the actual measured pressure; P0 is the saturated vapor pressure at the adsorption temperature; V is the adsorbed volume of nitrogen at pressure P; Vm is the volume of nitrogen required for monolayer saturated adsorption; and C is the thermal constant of adsorption.

[0031] The pore size distribution (Dp) of the sample is calculated by the BJH method (Barret-Joyner-Halensa) based on the capillary condensation phenomenon. k The radius of curvature of is related as follows:

[0032]

number

[0033] where r is 10 -5 is the surface tension of liquid nitrogen in N / cm; V m is the molar volume of liquid nitrogen; θ k is the contact angle between the meniscus and the solid pore wall; R is the ideal gas constant; T is the test temperature. The adsorption capacity V under different pressures P / P0 was obtained experimentally. V and r k The relationship between dV / dr and dr is given by equation (3-2). k By r k The result of plotting the above gives a curve of the pore size distribution of the sample.

[0034] In a preferred embodiment, the catalyst further comprises a promoter; more preferably, the promoter is a sulfur-containing compound, and preferably the sulfur-containing compound is derived from a sulfur-containing organic material.

[0035] Preferably, the support and active component supported thereon is a cocatalyst supported catalyst body.

[0036] In a further preferred embodiment, the content of the promoter in the catalyst is >0-1 wt%, preferably >0-0.8 wt%, where the amount of promoter is based on the amount of effective element therein (e.g., the amount of elemental sulfur).

[0037] In the present invention, the source of the sulfur-containing compound is not particularly limited, but is preferably at least one selected from the group including tert-nonyl polysulfide, tert-butyl polysulfide, thiophene, and dimethyl disulfide, but is not particularly limited.

[0038] Sulfur-containing compounds are preferentially adsorbed on the low-coordinated unsaturated active centers on the catalyst surface, which causes the local poisoning phenomenon of unstable active centers on the catalyst. In this way, the local overheating of the catalyst caused by the relatively high initial activity of the catalyst can be better suppressed, and the growth of metal particles and the excessive hydrogenation of isopropylbenzene to isopropylcyclohexane can be avoided. Meanwhile, the production of dimerized isopropylbenzene (2,3-dimethyl-2,3-diphenylbutane) can be effectively controlled, and the operational stability of the catalyst can be significantly improved while increasing the selectivity of isopropylbenzene.

[0039] The metallic palladium on the catalyst does not contain compressed double-bridged CO absorption sites. In situ infrared spectrograms of carbon monoxide adsorption on the catalyst show a peak at 2000–1950 cm -1 It is preferable that there is no absorption peak in the range.

[0040] In a preferred embodiment, the metallic palladium on the catalyst contains linearly bonded CO adsorption sites, single bridge-bonded CO adsorption sites, and surface-bound CO adsorption sites. In a further preferred embodiment, -1 , 1950~1900cm -1 and 1900~1850cm -1 Absorption peaks in the range of 0.1 to 1.0 μm are present in the in situ infrared spectrogram of carbon monoxide adsorption of the catalyst.

[0041] Generally, metal palladium catalysts are characterized by a CO-FTIR spectrogram with a band between 2150 and 2050 cm -1 ,2000~1950cm -1 ,1950~1900cm -1 and 1900~1850cm -1The Pd surface has four CO adsorption sites with special properties, which correspond to prominent absorption peaks in the range of 100 nm to 150 nm, respectively, which belong to a linear-bonded CO adsorption site, a compressed double-bridge-bonded CO adsorption site, a mono-bridge-bonded CO adsorption site, and a face-bonded CO adsorption site on the Pd surface.

[0042] The infrared spectrogram of CO adsorbed on the catalyst surface is measured as follows: CO Fourier transform infrared spectrogram (CO-FTIR): FT-IR study of CO adsorption was performed on a 4 cm -1 The measurements are carried out on an infrared analyzer (THERMO NICOLET 4700 NEXUS) with a resolution of 1000 nm. The samples are subjected to a pretreatment for reduction in a Harrick in situ pool. A background spectrogram is first scanned at the test temperature before introducing CO gas for adsorption. At the adsorption equilibrium, the sample is purged with nitrogen until no gas-phase infrared absorption peak of CO is detected. The infrared spectrograms at the measurement temperatures are collected and the background spectrograms at the corresponding temperatures are subtracted to obtain the infrared spectrogram of CO adsorbed on the catalyst surface.

[0043] A second aspect of the present invention provides a method for producing a catalyst according to the first aspect of the present invention, comprising the following steps: step 1: mixing an aqueous solution of a phosphorus-containing compound with a support substrate, drying, and calcining to obtain a phosphorus-containing support; step 2: adding the support to a solution of a palladium-containing compound, drying, and calcining to obtain a catalyst precursor in an oxidized state; step 3: subjecting the catalyst precursor in an oxidized state to a reduction treatment to obtain a catalyst.

[0044] In a preferred embodiment, step 1' is optionally performed after step 1 and before step 2: Step 1': mixing the phosphorus-containing support with an aqueous solution of silica gel, drying and calcining to obtain a support containing phosphorus and silicon. In a preferred embodiment, in steps 1, 2 and 1', drying is carried out at 60-200° C. for 4-36 hours, preferably at 150° C. for 6 hours, or preferably at 110° C. for 8 hours.

[0045] In a preferred embodiment, the firing temperature in steps 1, 2 and 1' is 400 to 700°C, and preferably 400 to 500°C.

[0046] In the present invention, the phosphorus-containing compound in step 1 is not particularly limited, and is preferably at least one selected from the group consisting of phosphoric acid, potassium dihydrogen phosphate, phosphorous acid, calcium phosphate, ammonium hydrogen phosphate, etc., but is not limited thereto.

[0047] In a preferred embodiment, the solution of the palladium-containing compound in step 2 further comprises a compound containing an active auxiliary metal.

[0048] In the present invention, unless otherwise specified, the support substrate is not particularly limited, but is preferably at least one selected from the group consisting of alumina, silica and activated carbon, more preferably alumina; the palladium-containing compound is not particularly limited, but is preferably at least one selected from the group consisting of palladium chloride, palladium nitrate and chloropalladium acid, but is not limited thereto; the compound containing an active auxiliary metal is not particularly limited, but is, for example, at least one selected from the group consisting of active auxiliary metal chloride, active auxiliary metal nitrate compound and active auxiliary metal acetate compound, but is not limited thereto; preferably, the active auxiliary metal is at least one selected from the group consisting of metallic copper, metallic zinc, metallic cobalt, metallic tin, metallic nickel and metallic silver, for example metallic copper.

[0049] In a preferred embodiment, in step 3, the reduction treatment is carried out with hydrogen. In a further preferred embodiment, the reduction temperature in step 3 is 40 to 300°C, preferably 200 to 300°C, more preferably 250°C; the volumetric space velocity of hydrogen is 50 to 500 h -1 , preferably 80 to 150 hours -1 , more preferably 100 h -1 It is.

[0050] In a preferred embodiment, the method further comprises step 4: Step 4: The catalyst from step 3 is added to a co-catalyst-containing solution and dried to obtain a further catalyst.

[0051] In a further preferred embodiment, the co-catalyst is a sulfur-containing compound; more preferably, the sulfur-containing compound is derived from a sulfur-containing organic material; further preferably, the sulfur-containing organic material is at least one selected from the group consisting of tert-nonyl polysulfide, tert-butyl polysulfide, thiophene, and dimethyl disulfide.

[0052] In the production method according to the present invention, the amounts of the palladium-containing compound and the phosphorus-containing compound are as follows, based on 1 L of the support substrate: the amount of the palladium-containing compound is preferably 0.06 g / L to 30 g / L, and more preferably 0.5 g / L to 10 g / L, based on the amount of the palladium element contained therein; and the amount of the phosphorus-containing compound is preferably 2 g / L to 100 g / L, and more preferably 5 g / L to 80 g / L, based on the amount of the phosphorus element contained therein.

[0053] If present, the amount of the compound containing the active auxiliary metal, silica gel and / or sulfur-containing organic material is as follows, based on 1 L of the support substrate: the amount of the compound containing the active auxiliary metal is preferably 0.0006 g / L to 1.2 g / L, more preferably 0.01 g / L to 1.0 g / L, based on the amount of the element of the active auxiliary metal contained therein; the amount of the silica gel is 6 to 300 g / L, preferably 20 to 200 g / L, the amount of the silica gel being based on the amount of silica contained therein; the amount of the promoter (e.g., sulfur-containing compound) is 0.0001 g / L to 3 g / L, preferably 0.01 g / L to 1 g / L, more preferably 0.05 g / L to 0.2 g / L, and the amount of the sulfur-containing compound is based on the amount of the effective element (e.g., elemental sulfur) contained therein.

[0054] In the process for preparing the catalyst of the present invention, all solutions are formed by completely dissolving the solutes in their good solvents, and are preferably aqueous solutions.

[0055] A third aspect of the present invention provides the use of a catalyst according to the first aspect of the present invention or a catalyst obtainable by the process according to the second aspect of the present invention in the manufacture of isopropylbenzene.

[0056] A fourth aspect of the present invention provides a process for the production of isopropylbenzene, in particular from α,α-dimethylbenzyl alcohol, preferably carried out using a catalyst according to the first aspect of the present invention or a catalyst obtained by the process according to the second aspect of the present invention.

[0057] In a preferred embodiment, the method includes contacting a feedstock with hydrogen and reacting in the presence of a catalyst to obtain isopropylbenzene. In a further preferred embodiment, the feedstock includes a hydrocarbon material containing α,α-dimethylbenzyl alcohol. In a further preferred embodiment, the hydrocarbon material containing α,α-dimethylbenzyl alcohol includes an inert solvent (preferably isopropylbenzene) and α,α-dimethylbenzyl alcohol. For example, the hydrocarbon material is the bottom liquid after propylene oxide is separated in the production of propylene oxide in the isopropylbenzene hydroperoxide process, and / or a material obtained from the reduction of isopropylbenzene hydroperoxide. Here, the inert solvent must be substantially inert to the reactants and products, such as, for example, long-chain alkanes (octane, dodecane) and aromatic monocyclic aromatic hydrocarbons (benzene, toluene, ethylbenzene, n-propylbenzene, n-butylbenzene, isopropylbenzene). Specifically, the inert solvent is a hydrocarbon that is substantially inert to the reactants and products. Furthermore, the solvent can be any organic solvent that has good compatibility with dimethylbenzyl alcohol, but is preferably isopropylbenzene, which does not affect the subsequent reaction.

[0058] In a preferred embodiment, the raw material contains 1-100% α,α-dimethylbenzyl alcohol and 0-99% inert solvent (preferably isopropylbenzene). In a more preferred embodiment, the raw material contains 50-75% α,α-dimethylbenzyl alcohol and 25-50% inert solvent (preferably isopropylbenzene).

[0059] In the present invention, the specific content of each component in the raw material is not particularly limited. As a non-limiting example, the raw material contains, based on weight percent, about 55% by weight of a hydrocarbon material of α,α-dimethylbenzyl alcohol, about 43% by weight of isopropylbenzene, and about 2% by weight of other hydrocarbons. The other hydrocarbons may include n-propylbenzene, methylstyrene, acetophenone, and 2,3-dimethyl-2,3-diphenylbutane.

[0060] In a preferred embodiment, in the production method, the pressure is 0.1 to 4.0 MPa, the temperature is 130 to 220° C., and the liquid hourly space velocity is 1 to 20 h -1 and the molar ratio of hydrogen to α,α-dimethylbenzyl alcohol is >4. In a more preferred embodiment, the pressure is 0.5-3.0 MPa, the temperature is 150-200°C, and the liquid hourly space velocity is 4-15 h -1 and the molar ratio of hydrogen to α,α-dimethylbenzyl alcohol is >5.

[0061] In a preferred embodiment, the preparation method uses liquid phase heat cycle treatment. Preferably, the cycle ratio is 1-10, preferably 4-8. Here, "liquid phase heat cycle treatment" refers to circulating the liquid phase heat material at the exhaust port of the catalyst bed directly to the catalyst bed without cooling and water separation.

[0062] In a preferred embodiment, the production process of the present invention comprises obtaining isopropylbenzene from a feedstock of a hydrocarbon material comprising α,α-dimethylbenzyl alcohol and hydrogen by passing it through a first catalyst bed and a second catalyst bed in succession, preferably by liquid-phase thermal cycling; wherein the catalyst loading of the first catalyst bed is greater than or equal to the catalyst loading of the second catalyst bed; the inlet temperature of the first catalyst bed is equal to or lower than the inlet temperature of the second catalyst bed; the liquid-phase thermal cycle ratio of the first catalyst bed is preferably 1-10; and the liquid-phase thermal cycle ratio of the second catalyst bed is preferably 0-2.

[0063] In a preferred embodiment, the volume ratio of the catalyst loading of the first catalyst bed to the catalyst loading of the second catalyst bed is (1-6):1, preferably (2-4):1.

[0064] In the first catalyst bed, the volume ratio of hydrogen to liquid phase is preferably 300-1000, more preferably 400-800, and / or in the second catalyst bed, the volume ratio of hydrogen to liquid phase is preferably 100-800, more preferably 200-400.

[0065] In a preferred embodiment, the first catalyst bed is subjected to a reaction temperature of 130 to 190° C., a reaction pressure of 0.1 to 5 MPa, and a reaction time of 1.0 to 20 h. -1 In a more preferred embodiment, the first catalyst bed has a reaction temperature of 150 to 170° C., a reaction pressure of 0.5 to 3.0 MPa, and a liquid hourly space velocity of 1 to 5 h. -1 and a cycle ratio of 2 to 8.

[0066] Here, the liquid phase is fresh oil, which refers to the raw material feed that is not diluted by liquid phase thermal cycle processing. In a preferred embodiment, the second catalyst bed is subjected to a reaction temperature of 150-230 ° C, a reaction pressure of 0.1-5 MPa, and a reaction time of 2.0-10 h. -1 In a more preferred embodiment, the second catalyst bed is heated at a reaction temperature of 160 to 190° C., at a reaction pressure of 0.5 to 3 MPa, and at a reaction temperature of 4 to 8 h. -1 The liquid hourly space velocity is

[0067] Preferably, the catalyst of the first catalyst bed comprises Pd metal and / or oxide, and a support.

[0068] Preferably, the catalyst of the second catalyst bed comprises metal Pd and / or oxide, a metal adjuvant and / or its oxide, and a support, preferably the metal adjuvant being at least one selected from the group consisting of Fe, Co, Ni, Ca, Mg and Cu, more preferably at least one selected from the group consisting of Cu, Ni and Mg.

[0069] Preferably, the catalyst of the first catalyst bed and / or the catalyst of the second catalyst bed is a catalyst as provided in the first aspect of the present invention and is a catalyst for producing isopropylbenzene.

[0070] In the present invention, the loading of the first catalyst bed is set equal to or greater than the loading of the second catalyst bed, preferably significantly higher than said loading, so that the raw material can react as much as possible in the first catalyst bed. If there is unreacted raw material, it will enter the second catalyst bed for reaction at a slightly higher temperature. Specifically, when the concentration of reactants in the raw material is high, the heat release in the reaction process is high, so the first bed uses the aspect of a liquid phase heat cycle with a high total volumetric space velocity and the function of carrying heat to prevent overheating of the bed and the formation of local hot spots, so as to contribute to the selectivity and stability of the catalyst. Meanwhile, the second bed using a higher temperature achieves a high conversion rate of a small amount of residual reactants. In this way, the impurity content in the product is significantly reduced.

[0071] In a preferred embodiment, in the process for producing isopropylbenzene from α,α-dimethylbenzyl alcohol, the conversion of α,α-dimethylbenzyl alcohol is greater than 99.5% and the selectivity of isopropylbenzene is greater than 99.8%.

[0072] The conversion and selectivity are calculated according to the following formulas: α,α-Dimethylbenzyl alcohol conversion rate (%) = [(W 0 1 -W t 1 ) / W 0 1 ] × 100%; Isopropylbenzene selectivity (%) = [((W t 2 -W 0 2 ) / M 2 ) / ((W 0 1 -W t 1 ) / M 1 )] × 100%; Here, w 0 1 is the mass of α,α-dimethylbenzyl alcohol in the raw material; w t 1 is the mass of α,α-dimethylbenzyl alcohol in the product; w 02 is the mass of isopropylbenzene in the raw material; w t 2 indicates the mass of isopropylbenzene in the product; M 1 is the molecular weight of α,α-dimethylbenzyl alcohol; M 2 indicates the molecular weight of isopropylbenzene.

[0073] The method for producing isopropylbenzene from α,α-dimethylbenzyl alcohol according to the present invention provides suitable dehydration sites and hydrogenation metal active sites, better inhibits the local overheating of the catalyst caused by the relatively high initial activity of the catalyst, and avoids the growth of metal particles and the over-hydrogenation of isopropylbenzene to isopropylcyclohexane in the catalytic process of producing isopropylbenzene by dehydration and hydrogenation of α,α-dimethylbenzyl alcohol in the presence of supported palladium active component. Meanwhile, it effectively controls the production of dimerized isopropylbenzene and significantly improves the operation stability of the catalyst while increasing the selectivity of isopropylbenzene.

[0074] The present invention further provides the use of said process, for example in the production of propylene oxide: Step 1: Oxidation of isopropylbenzene to obtain isopropylbenzene hydroperoxide; Step 2: Reaction of isopropylbenzene hydroperoxide with propylene to give propylene oxide and α,α-dimethylbenzyl alcohol; Step 3: Obtaining a hydrocarbon material containing α,α-dimethylbenzyl alcohol by means of separation of propylene oxide by rectification; Step 4: subjecting the hydrocarbon material comprising α,α-dimethylbenzyl alcohol to treatment with the catalyst and method of the present invention to obtain isopropylbenzene which is recycled to step 1 for reuse.

[0075] The endpoints of the ranges and any values ​​disclosed in the present invention are not limited to exact ranges or values. These ranges or values ​​should be interpreted as including these ranges or values ​​close to these values. With respect to numerical ranges, between the endpoints of each range, between the endpoints of each range and each individual value, and between each individual value, they can be combined with each other to obtain one or more new numerical ranges. These numerical ranges should be considered as specifically disclosed in the present invention. In principle, various technical solutions in the context can be combined with each other to obtain new technical solutions, which should also be considered as specifically disclosed in the present invention.

[0076] Compared with the prior art, the present invention has at least the following advantageous effects: (1) The addition of the reforming auxiliary component P into the support of the catalyst of the present invention can significantly improve and increase the hydrogenation activity and stability of the catalyst. In particular, when the molar ratio of silicon to phosphorus is constant, the addition of the reforming auxiliary component P and SiO 2 The addition of can significantly improve the hydrothermal stability of the catalyst.

[0077] (2) The simultaneous introduction of active auxiliary components into the catalyst can significantly improve the conversion of α,α-dimethylbenzyl alcohol and the selectivity of isopropylbenzene.

[0078] (3) By introducing a promoter into the catalyst, the excessive hydrogenation of isopropylbenzene to isopropylcyclohexane can be avoided, while the production of dimerized isopropylbenzene (2,3-dimethyl-2,3-diphenylbutane) can be effectively controlled, and the selectivity of isopropylbenzene can be increased while the operational stability of the catalyst can be significantly improved.

[0079] (4) The method for producing isopropylbenzene using a liquid phase heat cycle provided by the present invention can greatly reduce the energy consumption and cost of the equipment, and can efficiently produce isopropylbenzene, so that the utilization of reaction heat is more rational.

[0080] (5) The method for producing isopropylbenzene according to the present invention provides suitable dehydration sites and hydrogenation metal active sites, and better inhibits the excessive hydrogenation of isopropylbenzene to isopropylcyclohexane due to local overheating of the catalyst caused by the relatively high initial activity of the catalyst in the catalytic process for producing isopropylbenzene by dehydration and hydrogenation of α,α-dimethylbenzyl alcohol in the presence of supported palladium active catalyst. Meanwhile, it effectively controls the production of dimerized isopropylbenzene, and significantly improves the operational stability of the catalyst while increasing the selectivity of isopropylbenzene.

[0081] In conclusion, by preparing a carrier with good hydrothermal stability and excellent dehydration property, and using the carrier to support hydrogenation metals, the present invention provides a hydrocracking catalyst with good properties, realizes the combination of two reactions, dehydration and hydrogenation, and uses liquid phase heat cycle method to utilize energy more rationally. Meanwhile, the present invention prevents the deterioration of catalytic performance caused by local overheating of the catalyst bed, and realizes low-cost and highly efficient production of isopropylbenzene.

[0082] Modes for carrying out the invention.

[0083] The present invention will be described in detail in combination with the following specific examples. It should be noted that the following examples are only used to further illustrate the present invention and cannot be construed as limitations on the protection scope of the present invention. In addition, non-essential improvements and adjustments made by those skilled in the art to the present invention according to the content of the present invention are also within the protection scope of the present invention.

[0084] The ingredients of the raw materials used in the examples and comparative examples are shown in Table 1.

[0085] [Table 1]

[0086] Analysis of the content of each component in the catalyst: The composition of specific elements in the catalyst is measured by X-ray fluorescence spectrometry. Different elements have characteristic X-ray spectrograms with different wavelengths, and the fluorescence intensity of each spectral line has a specific relationship with the concentration of the element. By determining the wavelength and intensity of the characteristic X-ray spectral line of the element being tested, qualitative and quantitative analysis can be carried out.

[0087] I. Catalyst Preparation and Evaluation <Example 1> 1.Catalyst production A catalyst carrier was produced by mixing 1 L of alumina with 600 g of an aqueous phosphoric acid solution containing 8.0 g of P, drying at 110° C. for 8 hours, and calcining at 400° C. for 4 hours.

[0088] 1 L of the above support was mixed with 2000 g of a chloropalladium acid aqueous solution containing 3.0 g of palladium, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to produce an oxidized palladium-based catalyst precursor I. The above oxidized palladium-based catalyst precursor I was then heated for 100 hours. -1 The catalyst was reduced at 250°C for 4 hours using hydrogen at a volumetric space velocity of 10000 g / m2 to produce a palladium-based catalyst. The main components and properties of the catalyst are shown in Tables 2 and 3.

[0089] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0090] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0091] The physical properties of the catalyst after high temperature hydrothermal treatment are shown in Table 4.

[0092] <Example 2> 1.Catalyst production A catalyst support was produced by mixing 1 L of alumina with 600 g of an aqueous phosphoric acid solution containing 8.0 g of P, drying at 110° C. for 8 hours, and calcining at 400° C. for 4 hours.

[0093] 1 L of the above support was mixed with 2000 g of an aqueous solution of chloropalladium acid-copper nitrate containing 3.0 g of palladium and 1.0 g of copper, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to prepare oxidized palladium-based catalyst precursor I.

[0094] Palladium-based catalyst precursor I in the above oxidation state was -1 The mixture was reduced at 250° C. for 4 hours using hydrogen at a volumetric space velocity of 1000 g / m2 to produce a palladium-based catalyst.

[0095] The main components and properties of the catalyst are shown in Tables 2 and 3.

[0096] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0097] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0098] <Example 3> 1.Catalyst production A catalyst support was prepared by mixing 1 L of alumina with 600 g of an aqueous phosphoric acid solution containing 27 g of P, drying at 110° C. for 8 hours, and calcining at 400° C. for 4 hours.

[0099] 1 L of the above support was mixed with 2000 g of an aqueous solution of chloropalladium acid-copper nitrate containing 3.0 g of palladium and 1.0 g of copper, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to prepare oxidized palladium-based catalyst precursor I.

[0100] Palladium-based catalyst precursor I in the above oxidation state was -1 The mixture was reduced at 250° C. for 4 hours using hydrogen at a volumetric space velocity of 1000 g / m2 to produce a palladium-based catalyst.

[0101] The main components and properties of the catalyst are shown in Tables 2 and 3. The results of the CO-FTIR analysis are shown in Figure 1.

[0102] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0103] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0104] The physical properties of the catalyst after high temperature hydrothermal treatment are shown in Table 4.

[0105] <Example 4> 1.Catalyst production A catalyst support was prepared by mixing 1 L of alumina with 600 g of an aqueous phosphoric acid solution containing 35 g of P, drying at 110° C. for 8 hours, and calcining at 400° C. for 4 hours.

[0106] 1 L of the above support was mixed with 2000 g of an aqueous solution of chloropalladium acid-copper nitrate containing 3.0 g of palladium and 1.0 g of copper, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to prepare oxidized palladium-based catalyst precursor I.

[0107] Palladium-based catalyst precursor I in the above oxidation state was -1 The mixture was reduced at 250° C. for 4 hours using hydrogen at a volumetric space velocity of 1000 g / m2 to produce a palladium-based catalyst.

[0108] The main components and properties of the catalyst are shown in Tables 2 and 3.

[0109] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0110] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0111] The physical properties of the catalyst after high temperature hydrothermal treatment are shown in Table 4.

[0112] <Example 5> 1.Catalyst production A catalyst carrier was produced by mixing 1 L of alumina with 600 g of an aqueous phosphoric acid solution containing 5.0 g of P, drying at 110° C. for 8 hours, and calcining at 400° C. for 4 hours.

[0113] 1 L of the above support was mixed with 2000 g of an aqueous solution of chloropalladium acid-copper nitrate containing 3.0 g of palladium and 1.0 g of copper, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to prepare oxidized palladium-based catalyst precursor I.

[0114] Palladium-based catalyst precursor I in the above oxidation state was -1 The mixture was reduced at 250° C. for 4 hours using hydrogen at a volumetric space velocity of 1000 g / m2 to produce a palladium-based catalyst.

[0115] The main components and properties of the catalyst are shown in Tables 2 and 3.

[0116] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0117] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0118] The physical properties of the catalyst after high temperature hydrothermal treatment are shown in Table 4.

[0119] <Example 6> 1.Catalyst production A catalyst carrier was produced by mixing 1 L of alumina with 600 g of an aqueous phosphoric acid solution containing 27 g of P, drying at 110° C. for 8 hours, and calcining at 400° C. for 4 hours.

[0120] 1 L of the above support was mixed with 2000 g of an aqueous solution of chloropalladium acid-copper nitrate containing 3.0 g of palladium and 1.0 g of copper, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to prepare oxidized palladium-based catalyst precursor I.

[0121] Palladium-based catalyst precursor I in the above oxidation state was -1 The mixture was reduced at 250° C. for 4 hours using hydrogen at a volumetric space velocity of 1000 g / m2 to produce palladium-based catalyst precursor II.

[0122] 1 L of the above palladium-based catalyst precursor II was impregnated with 550 g of a cyclohexane solution of tert-nonyl polysulfide containing 0.1 g of sulfur, and dried at 110° C. to obtain a palladium-based catalyst.

[0123] The main components and properties of the catalyst are shown in Tables 2 and 3. The results of the CO-FTIR analysis are shown in Figure 1.

[0124] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0125] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0126] The physical properties of the catalyst after high temperature hydrothermal treatment are shown in Table 4.

[0127] <Example 7> 1.Catalyst production A catalyst carrier was produced by mixing 1 L of alumina with 600 g of an aqueous phosphoric acid solution containing 35 g of P, drying at 110° C. for 8 hours, and calcining at 400° C. for 4 hours.

[0128] 1 L of the above support was mixed with 2000 g of an aqueous solution of chloropalladium acid-copper nitrate containing 3.0 g of palladium and 1.0 g of copper, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to prepare oxidized palladium-based catalyst precursor I.

[0129] Palladium-based catalyst precursor I in the above oxidation state was -1 The mixture was reduced at 250° C. for 4 hours using hydrogen at a volumetric space velocity of 1000 rpm to produce palladium-based catalyst precursor II.

[0130] The above-mentioned palladium-based catalyst precursor II 1L was impregnated with 550 g of a cyclohexane solution of tert-nonyl polysulfide containing 0.1 g of sulfur, and dried at 110° C. to obtain a palladium-based catalyst. The main components and properties of the catalyst are shown in Tables 2 and 3.

[0131] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0132] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 1000-hour evaluation are shown in Table 5.

[0133] <Example 8> The process of Example 2 was repeated, except that the aqueous chloropalladate-nickel nitrate solution contained 10.0 g of palladium and 1.2 g of nickel. The main components of the catalyst are shown in Table 2.

[0134] The catalyst evaluation was repeated in Example 2. Similarly, the conversion of α,α-dimethylbenzyl alcohol and the selectivity for isopropylbenzene were both relatively high.

[0135] <Example 9> The process of Example 2 was repeated, except that the aqueous chloropalladate-cobalt nitrate solution contained 0.5 g palladium and 0.0006 g cobalt. The main components of the catalyst are shown in Table 2.

[0136] The catalyst evaluation was repeated in Example 2. Similarly, the conversion of α,α-dimethylbenzyl alcohol and the selectivity for isopropylbenzene were both relatively high.

[0137] <Examples 10-13> The procedure in Example 7 was repeated, except that di-tert-nonyl polysulfide containing 0.01 g, 0.05 g, 0.2 g and 1 g of sulfur was used, respectively. The main components of the catalyst are shown in Table 2.

[0138] The catalyst evaluation was repeated in Example 7. Similarly, the conversion of α,α-dimethylbenzyl alcohol and the selectivity for isopropylbenzene were both relatively high.

[0139] <Example 14> The process in Example 6 was repeated except for the preparation of the catalyst. In the preparation of the catalyst, 1 L of alumina was mixed with 600 g of an aqueous phosphoric acid solution containing 27 g of P, dried at 110° C. for 8 hours, and calcined at 400° C. for 4 hours to prepare a catalyst support containing P.

[0140] The above-mentioned P-containing catalyst carrier 1L was mixed with SiO 2 The mixture was mixed with 600 g of an aqueous silica gel solution having a mass concentration of 5%, dried, and then calcined at 500° C. to obtain a P / Si-containing carrier.

[0141] 1 L of the above-mentioned P / Si-containing support was mixed with 2000 g of an aqueous solution of chloropalladium acid-copper nitrate containing 3.0 g of palladium and 1.0 g of copper, dried at 110°C for 8 hours, and calcined at 500°C for 4 hours to produce oxidized palladium-based catalyst precursor I.

[0142] The palladium-based catalyst precursor I in the above oxidation state was heated at a volumetric space velocity of 100 h -1 The mixture was reduced with hydrogen for 4 hours at a reduction temperature of 250°C to obtain palladium catalyst precursor II.

[0143] The above palladium-based catalyst precursor II (1 L) was impregnated into 550 g of a cyclohexane solution of tert-nonyl polysulfide containing 0.1 g of sulfur to obtain a palladium-based catalyst. The main components of the catalyst are shown in Table 2.

[0144] The catalyst evaluation was repeated in Example 6. Similarly, the conversion of α,α-dimethylbenzyl alcohol and the selectivity for isopropylbenzene were both relatively high.

[0145] The physical properties of the catalyst after high temperature hydrothermal treatment are shown in Table 4.

[0146] <Example 15> The process of Example 6 was repeated except for the preparation of the catalyst. In the preparation of the catalyst, 600 g of an aqueous phosphoric acid solution containing 27 g of P was mixed with 1 L of alumina, dried at 110° C. for 8 hours, and calcined at 400° C. for 4 hours to prepare a catalyst support containing P.

[0147] SiO 2 600 g of an aqueous silica gel solution having a mass concentration of 10% was mixed with 1 L of the above-mentioned catalyst support containing P, dried, and then calcined at 500° C. to obtain a P / Si-containing support.

[0148] 1 L of the above-mentioned P / Si-containing support was mixed with 2000 g of an aqueous solution of chloropalladium acid-copper nitrate containing 3.0 g of palladium and 1.0 g of copper, dried at 110°C for 8 hours, and calcined at 500°C for 4 hours to produce oxidized palladium-based catalyst precursor I.

[0149] The palladium-based catalyst precursor I in the above-mentioned oxidation state was mixed at a volumetric space velocity of 100 h -1 The mixture was reduced with hydrogen for 4 hours at a reduction temperature of 250°C to obtain palladium catalyst precursor II.

[0150] The above palladium-based catalyst precursor II (1 L) was impregnated into 550 g of a cyclohexane solution of tert-nonyl polysulfide containing 0.1 g of sulfur to obtain a palladium-based catalyst. The main components of the catalyst are shown in Table 2.

[0151] The carrier obtained in Example 15 contained not only P but also silicon. In the production of isopropylbenzene by hydrogenation of α,α-dimethylbenzyl alcohol using the catalyst, the conversion rate of α,α-dimethylbenzyl alcohol and the selectivity of isopropylbenzene were both higher than those in Example 6.

[0152] The physical properties of the catalyst after high temperature hydrothermal treatment are shown in Table 4.

[0153] <Example 16> The process of Example 6 was repeated except for the preparation of the catalyst. In the preparation of the catalyst, 600 g of an aqueous phosphoric acid solution containing 27 g of P was mixed with 1 L of alumina, dried at 110° C. for 8 hours, and calcined at 400° C. for 4 hours to prepare a catalyst support containing P.

[0154] The above-mentioned P-containing catalyst carrier 1L was mixed with SiO 2 The mixture was mixed with 600 g of an aqueous silica gel solution having a mass concentration of 20%, dried, and then calcined at 500° C. to obtain a P / Si-containing carrier.

[0155] 1 L of the above-mentioned P / Si-containing support was mixed with 2000 g of an aqueous solution of chloropalladium acid-copper nitrate containing 3.0 g of palladium and 1.0 g of copper, dried at 110°C for 8 hours, and calcined at 500°C for 4 hours to produce oxidized palladium-based catalyst precursor I.

[0156] The palladium-based catalyst precursor I in the above-mentioned oxidation state was mixed at a volumetric space velocity of 100 h -1The mixture was reduced with hydrogen for 4 hours at a reduction temperature of 250°C to obtain palladium catalyst precursor II.

[0157] The above palladium-based catalyst precursor II (1 L) was impregnated into 550 g of a cyclohexane solution of tert-nonyl polysulfide containing 0.1 g of sulfur to obtain a palladium-based catalyst. The main components of the catalyst are shown in Table 2.

[0158] The physical properties of the catalyst after high temperature hydrothermal treatment are shown in Table 4.

[0159] <Example 17> The process in Example 6 was repeated except for the preparation of the catalyst. In the preparation of the catalyst, 1 L of alumina was mixed with 600 g of an aqueous phosphoric acid solution containing 27 g of P, dried at 110° C. for 8 hours, and calcined at 400° C. for 4 hours to prepare a catalyst support containing P.

[0160] The above-mentioned P-containing catalyst carrier 1L was mixed with SiO 2 The mixture was mixed with 600 g of an aqueous silica gel solution having a mass concentration of 30%, dried, and then calcined at 500° C. to obtain a P / Si-containing carrier.

[0161] 1 L of the above-mentioned P / Si-containing support was mixed with 2000 g of an aqueous solution of chloropalladium acid-copper nitrate containing 3.0 g of palladium and 1.0 g of copper, dried at 110°C for 8 hours, and calcined at 500°C for 4 hours to produce oxidized palladium-based catalyst precursor I.

[0162] The palladium-based catalyst precursor I in the above oxidation state was heated at a volumetric space velocity of 100 h -1 The mixture was reduced with hydrogen for 4 hours at a reduction temperature of 250° C. to produce palladium-based catalyst precursor II.

[0163] The above palladium-based catalyst precursor II (1 L) was impregnated into 550 g of a cyclohexane solution of tert-nonyl polysulfide containing 0.1 g of sulfur to obtain a palladium-based catalyst. The main components of the catalyst are shown in Table 2.

[0164] The physical properties of the catalyst after high temperature hydrothermal treatment are shown in Table 4.

[0165] Analysis of Examples 14-17: The supports used in the catalysts obtained in Examples 14-17 contained not only P, but also silicon and sulfur. When the above were used in the production of isopropylbenzene by hydrogenation of α,α-dimethylbenzyl alcohol, both the conversion of α,α-dimethylbenzyl alcohol and the selectivity of isopropylbenzene were higher than those in Example 6.

[0166] <Example 18> The process in Example 14 was repeated, except for the catalytic evaluation. In the catalytic evaluation, the hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously. The material was first passed through the first catalyst bed and then through the second catalyst bed. The catalyst loading volume ratio of the two catalyst beds was 4:1. The operating conditions of the two reactors were as follows: First catalyst bed: Inlet temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 2.0h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 Second catalyst bed: Inlet temperature: 160℃ Reaction pressure: 2.0MPa Liquid phase heat cycle ratio: 0 The average results of the 200-hour evaluation are shown in Table 5.

[0167] <Example 19> 1.Catalyst production A catalyst carrier was produced by mixing 1 L of alumina with 600 g of an aqueous phosphoric acid solution containing 8.0 g of P, drying at 110° C. for 8 hours, and calcining at 400° C. for 4 hours.

[0168] The above-mentioned P-containing catalyst carrier 1L was mixed with SiO 2The mixture was mixed with 600 g of an aqueous silica gel solution having a mass concentration of 10%, dried, and then calcined at 500° C. to obtain a P / Si-containing carrier.

[0169] 1 L of the above support was mixed with 2000 g of an aqueous chloropalladium acid solution containing 3.0 g of palladium, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to produce an oxidized palladium-based catalyst precursor I. The above oxidized palladium-based catalyst precursor I was heated at a volumetric space velocity of 100 h -1 The catalyst was reduced with 1000 ml of hydrogen for 4 hours at a reduction temperature of 250°C to produce a palladium-based catalyst. The main components and properties of the catalyst are shown in Tables 2 and 3.

[0170] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0171] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0172] The physical properties of the catalyst after high temperature hydrothermal treatment are shown in Table 4.

[0173] <Example 20> 1.Catalyst production A catalyst carrier was produced by mixing 1 L of alumina with 600 g of an aqueous phosphoric acid solution containing 8.0 g of P, drying at 110° C. for 8 hours, and calcining at 400° C. for 4 hours.

[0174] 1 L of the above support was mixed with 2000 g of an aqueous chloropalladium acid solution containing 3.0 g of palladium, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to prepare an oxidized palladium-based catalyst precursor I.

[0175] The palladium-based catalyst precursor I in the above oxidation state was heated at a volumetric space velocity of 100 h -1 The mixture was reduced with hydrogen for 4 hours at a reduction temperature of 250°C to obtain a palladium catalyst.

[0176] 1 L of the above-mentioned palladium-based catalyst precursor was impregnated with 550 g of a cyclohexane solution of tert-nonyl polysulfide containing 0.1 g of sulfur to obtain a palladium-based catalyst. The main components and properties of the catalyst are shown in Table 2.

[0177] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0178] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0179] <Example 21> 1.Catalyst production A catalyst carrier was produced by mixing 1 L of alumina with 600 g of an aqueous phosphoric acid solution containing 8.0 g of P, drying at 110° C. for 8 hours, and calcining at 400° C. for 4 hours.

[0180] The above-mentioned P-containing catalyst support 1L was mixed with SiO 2 The mixture was mixed with 600 g of an aqueous silica gel solution having a mass concentration of 10%, dried, and then calcined at 500° C. to obtain a P / Si-containing carrier.

[0181] 1 L of the above support was mixed with 2000 g of an aqueous chloropalladium acid solution containing 3.0 g of palladium, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to prepare an oxidized palladium-based catalyst precursor I.

[0182] The palladium-based catalyst precursor I in the above-mentioned oxidation state was mixed at a volumetric space velocity of 100 h -1 The mixture was reduced with hydrogen for 4 hours at a reduction temperature of 250°C to produce a palladium catalyst.

[0183] 1L of the above-mentioned palladium-based catalyst precursor was impregnated with 550g of a cyclohexane solution of tert-nonyl polysulfide containing 0.1g of sulfur to obtain a palladium-based catalyst. The main components and properties of the catalyst are shown in Tables 2 and 3.

[0184] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0185] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0186] The physical properties of the catalyst after high temperature hydrothermal treatment are shown in Table 4.

[0187] <Example 22> 1.Catalyst production A catalyst carrier was produced by mixing 1 L of alumina with 600 g of an aqueous phosphoric acid solution containing 8.0 g of P, drying at 110° C. for 8 hours, and calcining at 400° C. for 4 hours.

[0188] The above-mentioned P-containing catalyst support 1L was mixed with SiO 2The mixture was mixed with 600 g of an aqueous silica gel solution having a mass concentration of 10%, dried, and then calcined at 500° C. to obtain a P / Si-containing carrier.

[0189] 1 L of the above support was mixed with 2000 g of an aqueous solution of chloropalladium acid-copper nitrate containing 3.0 g of palladium and 1.0 g of copper, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to prepare oxidized palladium-based catalyst precursor I.

[0190] Palladium-based catalyst precursor I in the above oxidation state was -1 The catalyst was reduced at 250°C for 4 hours using hydrogen at a volumetric space velocity of 100000000000000 to produce a palladium-based catalyst. The main components of the catalyst are shown in Table 2.

[0191] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0192] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0193] <Example 23> 1.Catalyst production A catalyst carrier was produced by mixing 1 L of alumina with 600 g of an aqueous phosphoric acid solution containing 4.0 g of P, drying at 110° C. for 8 hours, and calcining at 400° C. for 4 hours.

[0194] The above-mentioned P-containing catalyst support 1L was mixed with SiO 2 The mixture was mixed with 600 g of an aqueous silica gel solution having a mass concentration of 10%, dried, and then calcined at 500° C. to obtain a P / Si-containing carrier.

[0195] 1 L of the above support was mixed with 2000 g of an aqueous solution of chloropalladium acid-copper nitrate containing 3.0 g of palladium and 1.0 g of copper, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to prepare oxidized palladium-based catalyst precursor I.

[0196] Palladium-based catalyst precursor I in the above oxidation state was -1 The catalyst was reduced at 250°C for 4 hours using hydrogen at a volumetric space velocity of 10000 g / m2 to produce a palladium-based catalyst. The main components and properties of the catalyst are shown in Tables 2 and 3.

[0197] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0198] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0199] The physical properties of the catalyst after high temperature hydrothermal treatment are shown in Table 4.

[0200] <Comparative Example 1> 1.Catalyst production 1 L of alumina was mixed with 2000 g of an aqueous chloropalladium acid solution containing 3.0 g of palladium, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to produce an oxidized palladium-based catalyst precursor I. The above-mentioned oxidized palladium-based catalyst precursor I was heated at a volumetric space velocity of 100 h -1 The mixture was reduced with hydrogen for 4 hours at a reduction temperature of 250°C to produce a palladium catalyst.

[0201] The main components and properties of the catalyst are shown in Tables 2 and 3.

[0202] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0203] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0204] The physical properties of the catalyst after high temperature hydrothermal treatment are shown in Table 4.

[0205] <Comparative Example 2> 1.Catalyst production 1 L of alumina was mixed with 2000 g of an aqueous solution of chloropalladium acid-copper nitrate containing 3.0 g of palladium and 1.0 g of copper, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to produce an oxidized palladium-based catalyst precursor I. The above-mentioned oxidized palladium-based catalyst precursor I was heated at a volumetric space velocity of 100 h -1 The mixture was reduced with hydrogen for 4 hours at a reduction temperature of 250°C to obtain a palladium catalyst.

[0206] The main components and properties of the catalyst are shown in Tables 2 and 3.

[0207] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0208] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0209] <Comparative Example 3> 1.Catalyst production 1 L of the alumina support was mixed with 2000 g of an aqueous solution of chloropalladium acid-copper nitrate containing 3.0 g of palladium and 1.0 g of copper, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to produce palladium-based catalyst precursor I in an oxidized state.

[0210] The palladium-based catalyst precursor I in the above oxidation state was heated at a volumetric space velocity of 100 h -1 The mixture was reduced with hydrogen for 4 hours at a reduction temperature of 250°C to produce a palladium catalyst.

[0211] The above palladium catalyst (1 L) was impregnated with 550 g of a cyclohexane solution of tert-nonyl polysulfide containing 0.1 g of sulfur to obtain a palladium catalyst. The main components of the catalyst are shown in Tables 2 and 3.

[0212] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0213] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0214] The physical properties of the catalyst after high temperature hydrothermal treatment are shown in Table 4.

[0215] <Comparative Example 4> 1.Catalyst production 1 L of the alumina support was mixed with 2000 g of an aqueous chloropalladium acid solution containing 3.0 g of palladium, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to produce an oxidized palladium-based catalyst precursor I.

[0216] The palladium-based catalyst precursor I in the above-mentioned oxidation state was mixed at a volumetric space velocity of 100 h -1 The mixture was reduced with hydrogen for 4 hours at a reduction temperature of 250°C to produce a palladium catalyst.

[0217] The above palladium catalyst (1 L) was impregnated with 550 g of a cyclohexane solution of tert-nonyl polysulfide containing 0.1 g of sulfur to obtain a palladium catalyst. The main components of the catalyst are shown in Tables 2 and 3.

[0218] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0219] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0220] <Comparative Example 5> 1.Catalyst production 1L of alumina support SiO 2 The mixture was mixed with 600 g of an aqueous silica gel solution having a mass concentration of 10%, dried, and then calcined at 500° C. to obtain a Si-containing support.

[0221] 1 L of the above support was mixed with 2000 g of an aqueous chloropalladium acid solution containing 3.0 g of palladium, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to prepare an oxidized palladium-based catalyst precursor I.

[0222] The palladium-based catalyst precursor I in the above oxidation state was heated at a volumetric space velocity of 100 h -1 The catalyst was reduced with hydrogen for 4 hours at a reduction temperature of 250°C to produce a palladium-based catalyst. The main components and characteristics of the catalyst are shown in Table 2.

[0223] The main components and properties of the catalyst are shown in Tables 2 and 3.

[0224] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0225] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0226] The physical properties of the catalyst after high temperature hydrothermal treatment are shown in Table 4.

[0227] <Comparative Example 6> 1.Catalyst production 1L of alumina support SiO 2 The mixture was mixed with 600 g of an aqueous silica gel solution having a mass concentration of 10%, dried, and then calcined at 500° C. to obtain a support containing Si.

[0228] 1 L of the above support was mixed with 2000 g of an aqueous chloropalladium acid solution containing 3.0 g of palladium, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to prepare an oxidized palladium-based catalyst precursor I.

[0229] The palladium-based catalyst precursor I in the above oxidation state was heated at a volumetric space velocity of 100 h -1 The mixture was reduced with hydrogen for 4 hours at a reduction temperature of 250°C to produce a palladium catalyst.

[0230] The above palladium catalyst (1 L) was impregnated with 550 g of a cyclohexane solution of tert-nonyl polysulfide containing 0.1 g of sulfur to obtain a palladium catalyst. The main components of the catalyst are shown in Table 2.

[0231] The main components and properties of the catalyst are shown in Table 2.

[0232] 2. Catalyst Evaluation The hydrogenation operation was carried out in a fixed bed reactor packed with the catalyst prepared as described above. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0233] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 200-hour evaluation are shown in Table 5.

[0234] [Table 2]

[0235] [Table 3]

[0236] [Table 4]

[0237] Table 4 shows that the physical properties of the catalysts of Examples 1, 3-6, 14-17, 19, 21 and 23 of the present invention after high temperature hydrothermal treatment are excellent.

[0238] [Table 5]

[0239] From Tables 2, 3, 4, 5 and Figure 1, at least the following can be seen:

[0240] (1) Comparing Example 1 with Comparative Example 1, the hydrothermal stability of the support was significantly improved, and the conversion rate of α,α-dimethylbenzyl alcohol and the selectivity of isopropylbenzene were significantly improved after adding phosphorus to the support.

[0241] (2) Comparing Example 1 and Example 2, when the Pd-Cu composite active component was used, the conversion rate of α,α-dimethylbenzyl alcohol and the selectivity of isopropylbenzene were both higher than those of the simple Pd active component.

[0242] (3) Comparing Example 1 and Example 19, the hydrothermal stability of the support was further improved, and the conversion rate of α,α-dimethylbenzyl alcohol and the selectivity of isopropylbenzene were further improved after introducing silica into the support.

[0243] (4) Comparing Example 1 and Example 20, the conversion of α,α-dimethylbenzyl alcohol and the selectivity of isopropylbenzene were further improved after introducing sulfur into the catalyst.

[0244] (5) Comparing Example 3 and Example 6, there was no compressed double cross-linked CO absorption site on the CO-FTIR spectrogram (see Figure 1). The production amount of isopropylcyclohexane was significantly reduced, and the conversion rate of α,α-dimethylbenzyl alcohol and the selectivity of isopropylbenzene were significantly improved after adding S to the catalyst.

[0245] (6) Comparing Examples 14-17 and Examples 1-13, respectively, when Cu, S, and Si were simultaneously introduced into the catalyst, the production amount of isopropylcyclohexane was significantly reduced.

[0246] (7) Comparing Example 18 with Example 14, the conversion rate of α,α-dimethylbenzyl alcohol and the selectivity of isopropylbenzene were significantly improved when the reaction process using two consecutive catalyst beds was used compared with the use of a single catalyst bed.

[0247] (8) All of the catalysts in Comparative Examples 3-6 did not contain phosphorus, and the conversion of α,α-dimethylbenzyl alcohol was poor, and the selectivity of isopropylbenzene was relatively low.

[0248] 1000 hours stability test: The hydrogenation operation was carried out in a fixed-bed reactor packed with the catalysts prepared in Example 14 and Comparative Example 1, respectively. The hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol was carried out continuously.

[0249] The operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 2.0MPa Volumetric space velocity of raw fresh oil: 1.6h -1 Liquid phase heat cycle ratio: 4 Hydrogen / α,α-dimethylbenzyl alcohol molar ratio: 8 The average results of the 1000-hour evaluation are shown in Table 6.

[0250] [Table 6]

[0251] 1000-hour stability tests were carried out on the catalysts prepared in Example 14 and Comparative Example 1, respectively. From Table 6, it can be seen that the catalyst of the present invention not only significantly reduced the production amount of isopropylcyclohexane at the initial activity stage of the catalyst, but also remained stable for 1000 hours with a conversion of α,α-dimethylbenzyl alcohol≧99.72% and a selectivity of isopropylbenzene≧99.88% in the evaluation of the 1000-hour reaction, indicating that the performance of the catalyst did not change significantly.

[0252] II. Method for Producing Isopropylbenzene from α,α-Dimethylbenzyl Alcohol As a result of the method for producing isopropylbenzene from α,α-dimethylbenzyl alcohol of the present invention, isopropylbenzene is produced from a feedstock of a hydrocarbon material containing α,α-dimethylbenzyl alcohol and hydrogen through a first catalyst bed and a second catalyst bed in succession, preferably by liquid-phase thermal cycle treatment. Related examples and comparative examples are listed as follows, but they cannot be construed as limitations of the present invention.

[0253] [Example 1'] 1.Catalyst production a. Preparation of the catalyst for the first catalyst bed 1 L of the alumina carrier was mixed with 2000 g of an aqueous chloropalladium acid solution containing 3.0 g of palladium, dried at 110° C. for 8 hours, and calcined at 450° C. for 4 hours to produce an oxidized palladium-based catalyst precursor I. The above-mentioned oxidized palladium-based catalyst precursor I was heated at a volumetric space velocity of 100 h -1 The catalyst was reduced with hydrogen for 4 hours at a reduction temperature of 300°C to produce a palladium catalyst. The main components of the catalyst are shown in Table 2'.

[0254] b. Preparation of the catalyst for the second catalyst bed 1 L of the alumina support was mixed with 2000 g of a chloropalladium acid-nickel nitrate aqueous solution containing 3.0 g of palladium and 0.3 g of nickel, dried at 110° C. for 8 hours, and calcined at 550° C. for 4 hours to produce an oxidized palladium-based catalyst precursor I. The above-mentioned oxidized palladium-based catalyst precursor I was heated at a volumetric space velocity of 100 h -1 The catalyst was reduced with hydrogen for 4 hours at a reduction temperature of 300°C to produce a palladium catalyst. The specific components of the catalyst are shown in Table 2'.

[0255] 2. Catalyst Evaluation The hydrogenation operation of the hydrocarbon material containing α,α-dimethylbenzyl alcohol of Table 1 was carried out continuously. The material was first passed through the first catalyst bed and then through the second catalyst bed. The catalyst loading volume ratio of the two catalyst beds was 4:1. The operating conditions of the two reactors were as follows: First catalyst bed: Reaction temperature: 150℃ Reaction pressure: 1.5MPa Volumetric space velocity of raw fresh oil: 2h -1 Liquid phase heat cycle ratio: 4 Hydrogen / raw fresh oil volume ratio: 400 Second catalyst bed: Reaction temperature: 170℃ Reaction pressure: 1.3MPa Hydrogen / raw fresh oil volume ratio: 200 The average results of the 200 hour evaluation are shown in Table 3'.

[0256] [Example 2'] 1.Catalyst production a. Preparation of the catalyst for the first catalyst bed 1 L of the alumina carrier was mixed with 2000 g of an aqueous chloropalladium acid solution containing 3.0 g of palladium, dried at 110° C. for 8 hours, and calcined at 450° C. for 4 hours to produce an oxidized palladium-based catalyst precursor I. The above-mentioned oxidized palladium-based catalyst precursor I was heated at a volumetric space velocity of 100 h -1 The catalyst was reduced with hydrogen for 4 hours at a reduction temperature of 300°C to produce a palladium catalyst. The main components of the catalyst are shown in Table 2'.

[0257] b. Preparation of the catalyst for the second catalyst bed 1 L of the alumina support was mixed with 2000 g of an aqueous solution of chloropalladium acid-nickel nitrate magnesium nitrate containing 3.0 g of palladium, 0.2 g of nickel, and 0.1 g of magnesium, dried at 110° C. for 8 hours, and calcined at 550° C. for 4 hours to produce an oxidized palladium-based catalyst precursor I. The oxidized palladium-based catalyst precursor I was heated at a volumetric space velocity of 100 h -1 The catalyst was reduced with hydrogen for 4 hours at a reduction temperature of 300°C to produce a palladium catalyst. The specific components of the catalyst are shown in Table 2'.

[0258] 2. Catalyst Evaluation The hydrogenation operation of the hydrocarbon material containing α,α-dimethylbenzyl alcohol of Table 1 was carried out continuously. The material was first passed through the first catalyst bed and then through the second catalyst bed. The catalyst loading volume ratio of the two catalyst beds was 4:1. The operating conditions of the two reactors were as follows: First catalyst bed: Reaction temperature: 150℃ Reaction pressure: 1.5MPa Volumetric space velocity of raw fresh oil: 2h -1 Liquid phase heat cycle ratio: 4 Hydrogen / raw fresh oil volume ratio: 400 Second catalyst bed: Reaction temperature: 170℃ Reaction pressure: 1.3MPa Hydrogen / raw fresh oil volume ratio: 100 Liquid phase heat cycle ratio: 0 The average results of the 200 hour evaluation are shown in Table 3'.

[0259] [Example 3'] 1.Catalyst production a. Preparation of the catalyst for the first catalyst bed 1 L of the alumina carrier was mixed with 2000 g of an aqueous chloropalladium acid solution containing 3.0 g of palladium, dried at 110° C. for 8 hours, and calcined at 450° C. for 4 hours to produce an oxidized palladium-based catalyst precursor I. The above-mentioned oxidized palladium-based catalyst precursor I was heated at a volumetric space velocity of 100 h -1The catalyst was reduced with hydrogen for 4 hours at a reduction temperature of 300°C to produce a palladium catalyst. The main components of the catalyst are shown in Table 2'.

[0260] b. Preparation of the catalyst for the second catalyst bed 1 L of the support catalyst was mixed with 2000 g of a chloropalladium acid-copper nitrate aqueous solution containing 3.0 g of palladium and 0.3 g of Cu, dried at 110° C. for 8 hours, and calcined at 550° C. for 4 hours to produce an oxidized palladium-based catalyst precursor I. The oxidized palladium-based catalyst precursor I was heated at a volumetric space velocity of 100 h -1 The catalyst was reduced with hydrogen for 4 hours at a reduction temperature of 300°C to produce a palladium catalyst. The specific components of the catalyst are shown in Table 2'.

[0261] 2. Catalyst Evaluation The hydrogenation operation of the hydrocarbon material containing α,α-dimethylbenzyl alcohol of Table 1 was carried out continuously. The material from which the heavy components were removed was first passed through the first catalyst bed and then through the second catalyst bed. The catalyst loading volume ratio of the two catalyst beds was 4:1. The operating conditions of the two reactors were as follows: First catalyst bed: Reaction temperature: 150℃ Reaction pressure: 1.5MPa Volumetric space velocity of raw fresh oil: 2h -1 Liquid phase heat cycle ratio: 4 Hydrogen / raw fresh oil volume ratio: 400 Second catalyst bed: Reaction temperature: 170℃ Reaction pressure: 1.3MPa Hydrogen / raw fresh oil volume ratio: 100 The average results of the 200 hour evaluation are shown in Table 3'.

[0262] [Example 4'] The process of Example 2 was repeated except for the preparation of the second catalyst: in the preparation of the second catalyst, an aqueous phosphoric acid solution 600 containing 60 g of P was mixed with 1 L of alumina, dried at 110° C. for 8 hours, and then calcined at 400° C. for 4 hours to prepare a catalyst support.

[0263] 2000 g of an aqueous solution of chloropalladium acid-copper nitrate containing 3.0 g of palladium and 1.0 g of copper was mixed with 1 L of the above-mentioned carrier, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to produce an oxidized palladium-based catalyst precursor.

[0264] The palladium-based catalyst precursor in the above oxidation state was then heated for 100 hours. -1 The mixture was reduced at a reduction temperature of 35° C. for 4 hours using hydrogen at a volumetric space velocity of 1000 g / m2 to produce a reduced palladium-based catalyst precursor.

[0265] 1 L of the above-mentioned reduced palladium-based catalyst precursor was impregnated with 550 g of a cyclohexane solution of tert-nonyl polysulfide containing 0.1 g of sulfur, and dried at 110° C. to obtain a catalyst. The main components of the catalyst and the average results of the 200-hour evaluation are shown in Tables 2' and 3', respectively.

[0266] [Example 5'] The process of Example 2 was repeated except for the preparation of the second-stage catalyst. In particular, in the preparation of the second-stage catalyst, 1 L of alumina was mixed with 27 g of phosphoric acid aqueous solution 600 containing P, dried at 110°C for 8 hours, and then calcined at 400°C for 4 hours to prepare a P-containing catalyst support.

[0267] 1 L of the above-mentioned P-containing catalyst carrier was mixed with SiO 2 Mix with 600g of silica gel aqueous solution, dry, and then bake at 500℃ to obtain P / SiO 2 A carrier containing the cellulose acetate was obtained.

[0268] 2000 g of chloropalladium acid-copper nitrate aqueous solution containing 3.0 g of palladium and 1.0 g of copper, and the above P / SiO 2 The mixture was mixed with 1 L of the carrier containing the palladium-based catalyst, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to produce an oxidized palladium-based catalyst precursor.

[0269] The palladium-based catalyst precursor in the above oxidation state was then heated for 100 hours. -1 The mixture was reduced at a reduction temperature of 35° C. for 4 hours using hydrogen at a volumetric space velocity of 1000 g / m2 to produce a reduced palladium-based catalyst precursor.

[0270] 1L of the above-mentioned reduced palladium-based catalyst precursor was impregnated into 550g of a cyclohexane solution of tert-nonyl polysulfide containing 0.1g of sulfur to obtain a palladium-based catalyst. The main components of the catalyst and the average results of the 200-hour evaluation are shown in Tables 2' and 3', respectively.

[0271] [Example 6'] The process of Example 5' was repeated except for the preparation of the second stage catalyst. In particular, in the preparation of the second catalyst, 1 L of alumina was mixed with 27 g of phosphoric acid aqueous solution 600 containing P, dried at 110°C for 8 hours, and then calcined at 400°C for 4 hours to prepare a P-containing catalyst support.

[0272] 2000 g of a chloropalladium acid-copper nitrate aqueous solution containing 3.0 g of palladium and 1.0 g of copper was mixed with 1 L of the above-mentioned P-containing support, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to produce an oxidized palladium-based catalyst precursor.

[0273] The palladium-based catalyst precursor in the above oxidation state was then heated for 100 hours. -1 The mixture was reduced at a reduction temperature of 35° C. for 4 hours using hydrogen at a volumetric space velocity of 1000 g / m2 to produce a reduced palladium-based catalyst precursor.

[0274] 1L of the above-mentioned reduced palladium-based catalyst precursor was impregnated into 550g of a cyclohexane solution of tert-nonyl polysulfide containing 0.1g of sulfur to obtain a palladium-based catalyst. The main components of the catalyst and the average results of the 200-hour evaluation are shown in Tables 2' and 3', respectively.

[0275] [Example 7'] The process of Example 5' was repeated except for the preparation of the second-stage catalyst. In particular, in the preparation of the second-stage catalyst, 1 L of alumina was mixed with 27 g of phosphoric acid aqueous solution 600 containing P, dried at 110°C for 8 hours, and then calcined at 400°C for 4 hours to prepare a P-containing catalyst support.

[0276] 1 L of the above-mentioned P-containing support was mixed with 2000 g of an aqueous solution of chloropalladium acid-copper nitrate containing 3.0 g of palladium and 1.0 g of copper, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to produce an oxidized palladium-based catalyst precursor.

[0277] The palladium-based catalyst precursor in the above oxidation state was then heated for 100 hours. -1 The mixture was reduced at 35° C. for 4 hours using hydrogen at a volumetric space velocity of 1000 g / m2 to produce a palladium-based catalyst.

[0278] The main components of the catalyst and the average results of the 200 hour evaluation are shown in Tables 2' and 3', respectively.

[0279] [Example 8'] The process of Example 5' was repeated except for the preparation of the second-stage catalyst. In particular, in the preparation of the second-stage catalyst, 1 L of alumina was mixed with 600 g of an aqueous phosphoric acid solution containing 27 g of P, dried at 110°C for 8 hours, and then calcined at 400°C for 4 hours to prepare a P-containing catalyst support.

[0280] 1 L of the above-mentioned P-containing support was mixed with 2000 g of an aqueous chloropalladium acid solution containing 3.0 g of palladium, dried at 110° C. for 8 hours, and calcined at 500° C. for 4 hours to prepare an oxidized palladium-based catalyst precursor.

[0281] The palladium-based catalyst precursor in the above oxidation state was then heated for 100 hours. -1 The catalyst was reduced at a reduction temperature of 35° C. for 4 hours using hydrogen at a volumetric space velocity of 10000 g / m2 to produce a palladium-based catalyst. The main components of the catalyst and the average results of the 200-hour evaluation are shown in Tables 2' and 3', respectively.

[0282] [Comparative Example 1'] 1.Catalyst production 1 L of the alumina support was mixed with 2000 g of an aqueous solution of chloropalladium acid-nickel nitrate containing 3.0 g of palladium and 0.3 g of nickel, dried at 110° C. for 8 hours, and calcined at 550° C. for 4 hours to produce an oxidized palladium-based catalyst precursor I. The above-mentioned oxidized palladium-based catalyst precursor I was heated at a volumetric space velocity of 100 h-1 The catalyst was reduced with hydrogen for 4 hours at a reduction temperature of 300°C to produce a palladium catalyst. The main components of the catalyst are shown in Table 2'.

[0283] 2. Catalyst Evaluation Hydrogenation of the hydrocarbon material containing α,α-dimethylbenzyl alcohol in Table 1 was carried out continuously. Only the material from which the heavy components were removed was passed through one catalyst bed. The catalyst loading of one catalyst bed was the same as that when two catalyst beds were used. The specific operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 1.50MPa Volumetric space velocity of raw fresh oil: 2h -1 Liquid phase heat cycle ratio: 4 Hydrogen / raw fresh oil volume ratio: 400 The average results of the 200 hour evaluation are shown in Table 3'.

[0284] [Comparative Example 2'] 1.Catalyst production 1 L of the alumina carrier was mixed with 2000 g of an aqueous chloropalladium acid solution containing 3.0 g of palladium, dried at 110° C. for 8 hours, and calcined at 450° C. for 4 hours to produce an oxidized palladium-based catalyst precursor I. The above-mentioned oxidized palladium-based catalyst precursor I was heated at a volumetric space velocity of 100 h -1 The catalyst was reduced with hydrogen for 4 hours at a reduction temperature of 300°C to produce a palladium catalyst. The main components of the catalyst are shown in Table 2'.

[0285] 2. Catalyst Evaluation Hydrogenation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol in Table 1 was carried out continuously. Only the material from which heavy components were removed was passed through one catalyst bed. The catalyst loading of one catalyst bed was the same as that when two catalyst beds were used. The specific operating conditions were as follows: Reaction temperature: 150℃ Reaction pressure: 1.50MPa Volumetric space velocity of raw fresh oil: 2h -1 Liquid phase heat cycle ratio: 4 Hydrogen / raw fresh oil volume ratio: 400 The average results of the 200 hour evaluation are shown in Table 3'.

[0286] [Comparative Example 3'] 1.Catalyst production a. Preparation of the catalyst for the first catalyst bed 1 L of the alumina carrier was mixed with 2000 g of an aqueous chloropalladium acid solution containing 3.0 g of palladium, dried at 110° C. for 8 hours, and calcined at 450° C. for 4 hours to produce an oxidized palladium-based catalyst precursor I. The above-mentioned oxidized palladium-based catalyst precursor I was heated at a volumetric space velocity of 100 h -1 The catalyst was reduced with hydrogen for 4 hours at a reduction temperature of 300°C to produce a palladium catalyst. The main components of the catalyst are shown in Table 2'.

[0287] b. Preparation of the catalyst for the second catalyst bed 1 L of the alumina support was mixed with 2000 g of an aqueous solution of chloropalladium acid-nickel nitrate containing 3.0 g of palladium and 0.3 g of nickel, dried at 110° C. for 8 hours, and calcined at 550° C. for 4 hours to produce an oxidized palladium-based catalyst precursor I. The above-mentioned oxidized palladium-based catalyst precursor I was heated at a volumetric space velocity of 100 h -1 The catalyst was reduced with hydrogen for 4 hours at a reduction temperature of 300°C to produce a palladium catalyst. The main components of the catalyst are shown in Table 2'.

[0288] 2. Catalyst Evaluation The hydrogenation operation of the hydrocarbon material containing α,α-dimethylbenzyl alcohol of Table 1 was carried out continuously. The material was first passed through the first catalyst bed and then through the second catalyst bed. The catalyst loading volume ratio of the two catalyst beds was 1:4. The operating conditions of the two reactors were as follows: First catalyst bed: Reaction temperature: 150℃ Reaction pressure: 1.50MPa Volumetric space velocity of raw fresh oil: 2h -1 Liquid phase heat cycle ratio: 4 Hydrogen / raw fresh oil volume ratio: 400 Second catalyst bed: Reaction temperature: 170℃ Reaction pressure: 1.3MPa Hydrogen / raw fresh oil volume ratio: 400 The average results of the 200 hour evaluation are shown in Table 3'.

[0289] [Comparative Example 4'] The preparation of the catalyst in Example 1' was repeated, except for the catalytic evaluation. In the catalytic evaluation, the hydrogenation operation of a hydrocarbon material containing α,α-dimethylbenzyl alcohol of Table 1 was carried out continuously. The material was first passed through the first catalyst bed and then through the second catalyst bed. The catalyst loading volume ratio of the two catalyst beds was 4:1. The operating conditions of the two reactors were as follows: First catalyst bed: Reaction temperature: 150℃ Reaction pressure: 1.50MPa Volumetric space velocity of raw fresh oil: 2h -1 Liquid phase heat cycle ratio: 0 Hydrogen / raw fresh oil volume ratio: 400 Second catalyst bed: Reaction temperature: 170℃ Reaction pressure: 1.3MPa Hydrogen / raw fresh oil volume ratio: 200 The average results of the 200 hour evaluation are shown in Table 3'.

[0290] [Table 7] JPEG0007599484000010.jpg125169

[0291] [Table 8]

[0292] From Tables 2' and 3' we can see that: (1) By comparing Comparative Example 1'-2' with Example 1' and Example 3', it can be determined that both Comparative Example 1'-2' use a single catalyst bed loaded with the same amount of catalyst, and the contents of isopropylbenzene hydroperoxide, α-methylstyrene, dimerized isopropylbenzene, and α,α-dimethylbenzyl alcohol in the product of Comparative Example 1'-2' are all higher than those of the Examples, especially the content of α,α-dimethylbenzyl alcohol. From the above, it is shown that the method according to the present invention can achieve high conversion to α,α-dimethylbenzyl alcohol. (2) By comparing Comparative Example 3' with Example 1', it can be determined that the catalyst loading in the first catalyst bed in Comparative Example 3' is lower than that in the second catalyst bed, and the contents of dimerized isopropylbenzene and α,α-dimethylbenzyl alcohol in the product of Comparative Example 3' are significantly higher.

[0293] (3) Comparing Example 5' with Example 3', when phosphorus, silica and sulfur were simultaneously introduced into the second catalyst, the content of isopropylbenzene hydroperoxide, the content of α-methylstyrene, the content of dimerized isopropylbenzene and the content of α,α-dimethylbenzyl alcohol in the product of Example 5' were all lower than those of Example 3'.

[0294] (4) Comparing Example 6' with Example 5', when only phosphorus and sulfur were introduced into the second catalyst, the content of isopropylbenzene hydroperoxide, the content of α-methylstyrene, the content of dimerized isopropylbenzene, and the content of α,α-dimethylbenzyl alcohol in the product of Example 6' were all higher than those of Example 5'.

[0295] (5) Comparing Example 7' with Example 5', when only phosphorus was introduced into the second catalyst, the content of isopropylbenzene hydroperoxide, the content of α-methylstyrene, the content of dimerized isopropylbenzene and the content of α,α-dimethylbenzyl alcohol in the product of Example 7' were all higher than those of Example 5'.

[0296] (6) Comparing Example 8' with Example 7', when only phosphorus was introduced into the second catalyst, the content of isopropylbenzene hydroperoxide, the content of α-methylstyrene, the content of dimerized isopropylbenzene and the content of α,α-dimethylbenzyl alcohol in the product of Example 8' were all higher than those of Example 7'.

[0297] (7) Comparing Comparative Example 4' with Example 1', it can be determined that although the liquid phase heat cycle ratio of the first catalyst bed under the operating conditions of the reactor in Comparative Example 4' was 0, the content of dimerized isopropylbenzene in the product in Comparative Example 4' was significantly high, and the selectivity of isopropylbenzene was significantly reduced. [Brief description of the drawings]

[0298]

Claims

1. A catalyst for producing isopropylbenzene from α,α-dimethylbenzyl alcohol, comprising: The composition includes a carrier and an active ingredient supported on the carrier, The support includes a support substrate and a modifying auxiliary component supported on the support substrate, A catalyst wherein said active component comprises metallic palladium and / or its oxide and said modifying auxiliary component comprises phosphorus and / or its oxide.

2. Catalyst according to claim 1, characterized in that the content of said metallic palladium and / or its oxide in the catalyst is 0.01-5 wt. % based on the content of palladium element and / or the metallic palladium has a degree of dispersion of 5-10%.

3. The active component further comprises an active auxiliary metal and / or an oxide thereof. The catalyst according to claim 2.

4. The active auxiliary metal is at least one selected from the group consisting of metallic copper, metallic zinc, metallic cobalt, metallic tin, metallic nickel and metallic silver; and / or The content of the active auxiliary metal and / or its oxide in the catalyst is 0.0001-0.2 wt. % based on the content of the auxiliary metal element therein; The catalyst according to claim 3.

5. 5. The catalyst according to claim 1, wherein the content of the reforming auxiliary component in the catalyst is 0.2 to 20% by weight based on the content of phosphorus element.

6. The support substrate is at least one selected from the group consisting of silica, alumina and activated carbon, and / or the support substrate has a pore size of 10 to 25 nm and a pore size of 50 to 180 nm. 2 The catalyst according to any one of claims 1 to 5, characterized in that it has a specific surface area of ​​1 / g.

7. The catalyst according to any one of claims 1 to 6, characterized in that the catalyst further comprises a promoter.

8. the cocatalyst is a sulfur-containing compound; and / or 8. The catalyst of claim 7, wherein the content of the promoter in the catalyst is >0-1 wt.%, and the amount of the promoter is based on the amount of effective element therein.

9. The catalyst according to any one of claims 1 to 8, characterized in that, if silica is not the support substrate, the modifying auxiliary component further comprises silica.

10. When silica is not the support substrate, the modified auxiliary component further comprises silica; the molar ratio of silicon to phosphorus, on an elemental basis, is ≦20; The content of phosphorus and / or its oxide in the reforming auxiliary component in the catalyst is 0.2 to 20% by weight, Catalyst according to any one of claims 1 to 9, characterized in that the content of phosphorus and / or its oxides is based on the content of elemental phosphorus therein and the silica content in the catalyst is >0-60 wt.-%.

11. the molar ratio of silicon to phosphorus, on an elemental basis, is ≦10; and / or The content of phosphorus and / or its oxides in the reforming auxiliary component in the catalyst is 1-15 wt. %, the content of phosphorus and / or its oxides being based on the content of phosphorus element therein; and / or The silica content in the catalyst is >0-40 wt.%; The catalyst according to claim 10, characterized in that

12. the molar ratio of silicon to phosphorus, on an elemental basis, is ≦4; and / or The content of phosphorus and / or its oxides in the reforming auxiliary component in the catalyst is 1-7 wt. %, the content of phosphorus and / or its oxides being based on the content of phosphorus element therein; and / or The silica content in the catalyst is >0-20 wt.%; The catalyst according to claim 11 .

13. A method for producing the catalyst according to any one of claims 1 to 12, comprising the steps of: Step 1: Mix an aqueous solution of a phosphorus-containing compound with a support substrate, dry, and then calcinate to obtain a phosphorus-containing support; Step 2: Add the support to a solution of a palladium-containing compound, dry, and calcinate to obtain an oxidized catalyst precursor; Step 3: The catalyst precursor in an oxidized state is subjected to a reduction treatment to obtain a catalyst.

14. The support substrate is at least one selected from the group consisting of silica, alumina and activated carbon, and / or the palladium-containing compound is at least one selected from the group consisting of palladium chloride, palladium nitrate and chloropalladic acid; and / or the phosphorus-containing compound is at least one selected from the group consisting of phosphoric acid, potassium dihydrogen phosphate, phosphorous acid, calcium phosphate and ammonium hydrogen phosphate; and / or The method according to claim 13, wherein the solution in step 2 further comprises a compound containing an active auxiliary metal.

15. In steps 1 and 2, the firing temperature is 400 to 700° C., and / or 15. The method according to claim 13 or 14, wherein in step 3, the reduction treatment is carried out using hydrogen.

16. The process according to any one of claims 13 to 15, characterized in that step 1' is carried out after step 1 and before step 2: Step 1': The phosphorus-containing support is mixed with an aqueous solution of silica gel, dried and calcined to obtain a support containing phosphorus and silicon.

17. The method according to any one of claims 13 to 16, further comprising step 4: Step 4: The catalyst described in step 3 is added to a co-catalyst-containing solution and dried to obtain further catalyst.

18. Based on the carrier substrate 1L, the amount of the palladium-containing compound is from 0.06 g / L to 30 g / L based on the amount of elemental palladium contained therein; and / or the amount of the compound containing the active auxiliary metal is 0.0006 g / L to 1.2 g / L based on the amount of the element of the active auxiliary metal contained therein; and / or the amount of the phosphorus-containing compound is from 2 g / L to 100 g / L based on the amount of elemental phosphorus contained therein; and / or 15. The method of claim 14, wherein the amount of silica gel is 6-300 g / L, and the amount of silica gel is based on the amount of silica contained therein.

19. Use of the catalyst according to any one of claims 1 to 12 or the catalyst obtainable by the process according to any one of claims 13 to 18 in the production of isopropylbenzene from α,α-dimethylbenzyl alcohol.

20. A process for producing isopropylbenzene from α,α-dimethylbenzyl alcohol, the process being carried out in the presence of a catalyst according to any one of claims 1 to 12, or a catalyst obtained by the process according to any one of claims 13 to 18.

21. The method for producing the isopropylbenzene includes contacting a feedstock with hydrogen and reacting it in the presence of a catalyst to obtain isopropylbenzene, and the method uses a liquid phase thermal cycle process having a cycle ratio of 1 to 10. The method of claim 20.

22. the feedstock comprises a hydrocarbon material comprising α,α-dimethylbenzyl alcohol; 22. The method of claim 21, wherein the hydrocarbon material optionally comprises isopropylbenzene, acetophenone, alpha-methylstyrene and dimerized isopropylbenzene, and optionally comprises isopropylbenzene hydroperoxide.

23. In the above-mentioned production method, the pressure is 0.1 to 4.0 MPa, the temperature is 130 to 220° C., and the liquid hourly space velocity is 1 to 20 h -1 23. The process according to claim 22, characterized in that the molar ratio of hydrogen to α,α-dimethylbenzyl alcohol is >4.

24. A method for producing isopropylbenzene from α,α-dimethylbenzyl alcohol, comprising the steps of: obtaining isopropylbenzene from a feed of hydrocarbon material comprising α,α-dimethylbenzyl alcohol and hydrogen, through a first catalyst bed and a second catalyst bed in series; the catalyst loading of the first catalyst bed is greater than or equal to the catalyst loading of the second catalyst bed; the inlet temperature of the first catalyst bed is less than or equal to the inlet temperature of the second catalyst bed; A process for producing a catalyst, wherein the catalyst of the first catalyst bed and / or the catalyst of the second catalyst bed is a catalyst according to any one of claims 1 to 12.

25. The method of claim 24 is carried out by a liquid phase thermal cycle treatment; and / or the volumetric ratio of the catalyst loading of the first catalyst bed to the catalyst loading of the second catalyst bed is (1-6):1; and / or The first catalyst bed is subjected to a reaction temperature of 130 to 190° C., a reaction pressure of 0.1 to 5 MPa, and a reaction time of 1.0 to 20 h. -1 and / or the second catalyst bed has a reaction temperature of 150 to 230° C., a reaction pressure of 0.1 to 5 MPa, and a liquid hourly space velocity of 2.0 to 10 h -1 and / or The liquid phase heat cycle ratio of the first catalyst bed is between 1 and 10; and / or The process of claim 24, wherein the liquid phase heat cycle ratio of the second catalyst bed is between 0 and 2.

26. 26. The process of claim 25, wherein in the first catalyst bed the volume ratio of hydrogen to the liquid phase is between 300 and 1000, and / or in the second catalyst bed the volume ratio of hydrogen to the liquid phase is between 100 and 800.

27. 27. The process according to any one of claims 24 to 26, wherein the catalyst of the first catalyst bed comprises metallic Pd and / or an oxide, and a support, and / or the catalyst of the second catalyst bed comprises metallic Pd and / or an oxide, a metal auxiliary and / or its oxide, and a support.

28. Use of the process according to any one of claims 20 to 27 in the production of propylene oxide.

Citation Information

Patent Citations

  • Alpha-methyl styrene selective hydrogenation method

    CN104151129A

  • Alpha, alpha-dimethylbenzyl alcohol hydrogenolysis method for preparing isopropyl benzene

    CN104230640A

  • Production method of isopropyl benzene

    CN104230641A

  • Selective hydrogenation of alpha-methyl-styrene to cumene

    JP2006176492A

  • Catalyst for producing cumene and its application

    JP2019005746A